Analisis Keterampilan Berbicara dalam Dakwah Ustadz Hanan Attaki - Desmiyati Desmiyati; Supriyadi Supriyadi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The problems studied in this research are linguistic factors and non-linguistic factors in Ustadz Hanan Attaki's lecture. The research method is descriptive qualitative. The data analysis technique used is to reduce the presentation of the data and draw conclusions. On the linguistic factor in Ustad Hanan Attaki's da'wah on the aspect of pronunciation accuracy, Ustadz Hanan Attaki articulates language signs effectively. Placement of stress, placing language pressure properly and appropriately. The accuracy of pressure, tone, joints and duration have become the main attraction of Ustadz Hanan Attaki's da'wah in delivering his da'wah which is quite an expression. In the choice of words, in addition to using the official language in accordance with the EYD, also using an unofficial language. The accuracy of the target of the conversation is effective in the application of sentences in carrying out a communication. Non-linguistic factors in the aspect of a reasonable, calm and not rigid attitude that Ustadz Hanan Attaki's expression appears in a normal body posture. In the aspect of loudness, adjusting the number of worshipers with the loudspeakers used, this is evidenced by adjusting the response of the congregation to the things conveyed by Ustadz Hanan Attaki. The aspect of fluency, has been very smooth and very mastered the atmosphere of da'wah. it's just that in preaching, sounds like /e/, /anu/, /em/ are still inserted.